Ijarah Financing Model for Farmers' Capital with a Post-Harvest Return System - Indawati, Indawati; Rusly, Fathullah; Norhayati, Norhayati (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The aim of this research is to determine the ijarah financing model for farmers’ capital with a post-harvest return system at BMT Maslahah Cabang Krucil. This research uses qualitative methods with data collection methods in the form of observation, interviews and documentation. One of the financing products offered by BMT Maslahah Cabang Krucil is ijarah financing with a post-harvest repayment system whose aim is to make it easier for farmers to obtain capital. Members who borrow capital with a post-harvest repayment system can return the capital they have borrowed in several harvests and the collateral required is also not that difficult, but BMT Maslahah The Krucil Branch continues to apply caution in providing loans. So this is one of the factors of public interest in ijarah financing with a post-harvest repayment system and at BMT Maslahah, the Krucil Branch does not apply an interest system but applies a profit sharing system. Where members can pay profit sharing. At the beginning of the loan period or paying in installments every month but cannot pay in full at the end of the due date.